MUSIK DAN PEMATANGAN DINI JIWA ANAK - Cipto Budy Handoyo (FBS UNY, 2012)
Music cannot be separated from human life, and it has been attached to people from generation to generation in all periods of time. Therefore, music logically influences human life as the civilization develops both in positive and in negative ways. The negative influences can cause the human beings’ “early maturity”. Commonly, negative influences have the power to affect people more easily, and this also happens in music. Music can easily inspire people, especially the young, in a negative way. For example, when children enjoy a certain kind of music with all its negative performance and style, they will be easily stimulated by what they see. Thus, people generally expect to gain the positive effects from music. In doing so, there is a huge responsibility for us to think about the way music can give positive contributions especially for the young. In this case, we should optimistically guide children to choose the right kinds of music for them so that we can help them develop their mind for their bright future.